2019
DOI: 10.1021/acs.jnatprod.9b00603
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Protocol for Accurately Calculating 13C Chemical Shifts of Conformationally Flexible Natural Products: Scope, Assessment, and Limitations

Abstract: An efficient protocol for calculating 13C NMR chemical shifts for natural products with multiple degrees of conformational freedom is described. This involves a multistep procedure starting from molecular mechanics and ending with a large basis set density functional model to obtain accurate Boltzmann conformer weights, followed by empirically corrected density functional NMR calculations for the individual conformers. The accuracy of the protocol (average rms <4 ppm) was determined by application to ∼925 dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
132
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(146 citation statements)
references
References 45 publications
4
132
0
Order By: Relevance
“…These calculations were performed as implemented in Spartan'18 ("Spartan'18, 2019"). An automated version of this approach has been described (Hehre et al, 2019) in which accurate Boltzmann weighting of conformationally flexible molecules was reported. The 10 lowest energy conformations were next refined using the M06−2X density functional theory (DFT) method and the 6−31+G(d) basis set, with the GD3 empirical dispersion correction.…”
Section: Methodsmentioning
confidence: 99%
“…These calculations were performed as implemented in Spartan'18 ("Spartan'18, 2019"). An automated version of this approach has been described (Hehre et al, 2019) in which accurate Boltzmann weighting of conformationally flexible molecules was reported. The 10 lowest energy conformations were next refined using the M06−2X density functional theory (DFT) method and the 6−31+G(d) basis set, with the GD3 empirical dispersion correction.…”
Section: Methodsmentioning
confidence: 99%
“…[124] Provided that there are a limited number of possible stereoisomers for a compound whose skeletal structure is known, it may be possible to use DFT calculations for each isomer to estimate the relative energies and 13 C chemical shifts for each of the local minima on its potential energy surface. [125] Then, the weight average chemical shifts for each of them can be compared with experimental values in the hope that this will identify the most probable stereoisomer. However, depending upon the number of possible choices, this can be a very slow process.…”
Section: Determining Stereochemistry Can Be Particularly Trickymentioning
confidence: 99%
“…However, depending upon the number of possible choices, this can be a very slow process. [ 125 ] When this approach was applied to compounds whose previously reported structures had been deduced from only NMR data, 5 to 10% of them gave very poor agreement between calculated and experimental chemical shifts. This suggested that their reported stereochemistries (or possibly their skeletal structures) were wrong and that structure revisions were needed.…”
Section: Determining Stereochemistry Can Be Particularly Trickymentioning
confidence: 99%
See 1 more Smart Citation
“…for the prediction of 13 C chemical shifts of flexible compounds [24]. For the two diastereomers, 6 or 10 conformers were found with detectable populations at room temperature.…”
mentioning
confidence: 95%